2009
DOI: 10.1080/13607860902867750
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of the British evacuation of children during World War 2 on their adult mental health

Abstract: The study demonstrated significant associations between childhood experiences and lifespan mental health, reinforcing the importance of knowledge of childhood history in the clinical treatment of older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…In long-term studies of children evacuated and separated from their parents during World War II bombings in Europe, increased rates of mental health problems have been reported 6 to 7 decades after the experience. 32,33 However, Finnish adults who were separated from their father in World War II because of military deployment had no adult mental health sequelae because of their experience, which is in contrast to children separated from their parents as a result of evacuation. 33 Our study was limited by reliance on clinical diagnosis and provider coding for identification of mental and behavioral health diagnoses and not on standardized clinical definitions.…”
Section: Male) Of Deployed Marines In 2003mentioning
confidence: 95%
“…In long-term studies of children evacuated and separated from their parents during World War II bombings in Europe, increased rates of mental health problems have been reported 6 to 7 decades after the experience. 32,33 However, Finnish adults who were separated from their father in World War II because of military deployment had no adult mental health sequelae because of their experience, which is in contrast to children separated from their parents as a result of evacuation. 33 Our study was limited by reliance on clinical diagnosis and provider coding for identification of mental and behavioral health diagnoses and not on standardized clinical definitions.…”
Section: Male) Of Deployed Marines In 2003mentioning
confidence: 95%
“…This enabled the study of child-parent separation. One of these studies reported lower psychological well-being and insecure attachment styles (Foster et al, 2003) along with heightened risk of depression and anxiety (Rusby and Tasker, 2009). Other studies found no change in depression, anxiety, or mental health (Birtchnell and Kennard, 1984;Tennant et al, 1982).…”
Section: Discussionmentioning
confidence: 97%
“…Abuse, neglect, and separation from either one or both parents during childhood have been shown to be associated with a greater risk of mental health disorders (Afifi et al, 2006(Afifi et al, , 2009Danese et al, 2009;Green et al, 2010;Hjern et al, 2002;Johnson et al, 1999Johnson et al, , 2006M€ akikyr€ o et al, 1998;Morgan et al, 2007;Pesonen et al, 2007;Rubino et al, 2009;Rusby and Tasker, 2009;Sharon et al, 2009;Thompson et al, 2008;Tieman et al, 2005;Veijola et al, 2004Veijola et al, , 2008Widom, 1999;Widom et al, 2007Widom et al, , 2009. Also parental separation during childhood has been shown to have detrimental psychological long-term consequences (Birtchnell and Kennard, 1984;Breier et al, 1988;Foster et al, 2003;Kendler et al, 1992Kendler et al, , 2002Pesonen et al, 2007;Tennant et al, 1982).…”
mentioning
confidence: 95%
“…Capstick and Clegg's (2013) study of the war narratives of three men with dementia also notes that historical trauma can be reactivated with the onset of dementia due to a relaxation of cognitive control over emotional memory, and that this can lead to the emergence of counter-hegemonic versions of historical events. Rusby and Tasker (2009) found that wartime evacuation could have lifelong effects on mental health and well-being, with age at the time and quality of care being significant 8 factors. Cook et al (2003) note that many aspects of a care environment may act as reminders of traumatic experiences, including television news coverage, the sound of other people in distress, and loud noises.…”
Section: Psychogeography and Dementiamentioning
confidence: 99%